Answers
Answered by
0
Heya!✋
Here is your answer.
=================================
Given that,
x²+1\x²=6
The given equation,
( x²)²+ 1\(x²)²
=> (x²+1\x²)²-2×x²×1\x² [a²+b²=(a+b)²-2ab]
=> (6)²- 2
=> 36-2
=> 34
[Answer]
==================================
Friend, I hope that you can solve such type of math.
Here is your answer.
=================================
Given that,
x²+1\x²=6
The given equation,
( x²)²+ 1\(x²)²
=> (x²+1\x²)²-2×x²×1\x² [a²+b²=(a+b)²-2ab]
=> (6)²- 2
=> 36-2
=> 34
[Answer]
==================================
Friend, I hope that you can solve such type of math.
jmsbrothers:
thanks, can you mark it as brainliest? :)
Similar questions